Competency in network use as a resource for citizenship: implications for the digital divide - Jääskeläinen; Pirkko; Savolainen; Reijo (Information Research: An International Electronic Journal, 2003)
Conceptual and empirical issues of citizens' network ompetency are explored, defined as people's capabilities to use the Internet in order to communicate and seek information and to utilize electronic public services. First, the concept of network competency is discussed. Second, based on an empirical case study conducted in Finland, perceived network competency is explored as a resource for autonomous and participatory citizenship. Perceived network competency refers to the self-rated assessment made by the informants. A high degree of perceived network competency correlated positively with success in work life. Network competent people participated more frequently in the activities of civic organizations and contacted decision-makers. Compared to less competent people, they appeared to be informed consumers. Those with high perceived competency believed that people's opportunities to influence social issues will increase in the future. The findings are explored with regard to the digital divide vs. digital inclusion, discussing the prospects for future research.